2019
DOI: 10.1002/anie.201900511
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Triazole Urea Activity‐Based Probes for the Single‐Cell Phenotypic Characterization of Staphylococcus aureus

Abstract: Phenotypically distinct cellular (sub)populations are clinically relevant for the virulence and antibiotic resistance of abacterial pathogen, but functionally different cells are usually indistinguishable from eacho ther.H erein, we introduce fluorescent activity-based probes as chemical tools for the single-cell phenotypic characterization of enzyme activity levels in Staphylococcus aureus.W es creened a1 ,2,3-triazole urea library to identify selective inhibitors of fluorophosphonate-binding serine hydrolase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 22 publications
7
47
0
Order By: Relevance
“…This included obvious candidates such as esterases and efflux pumps, but also identified a mycobacterial divisome factor responsible for heterogeneity in polar growth. [103] Target-selective probes can also serve as reporters for phenotypic heterogeneity in bacterial population as our already mentioned studies on the distribution of the enzymatic activities of the S. aureus serine virulence factors FphB and FphE across growth conditions revealed [7,84]. While the physiological relevance and molecular mechanisms behind this observation remain unclear, it showcases how the use of chemical probes in cellular imaging can uncover new biology-both by design and by serendipity.…”
Section: Biofilms and Other Microbial Communitiesmentioning
confidence: 84%
See 3 more Smart Citations
“…This included obvious candidates such as esterases and efflux pumps, but also identified a mycobacterial divisome factor responsible for heterogeneity in polar growth. [103] Target-selective probes can also serve as reporters for phenotypic heterogeneity in bacterial population as our already mentioned studies on the distribution of the enzymatic activities of the S. aureus serine virulence factors FphB and FphE across growth conditions revealed [7,84]. While the physiological relevance and molecular mechanisms behind this observation remain unclear, it showcases how the use of chemical probes in cellular imaging can uncover new biology-both by design and by serendipity.…”
Section: Biofilms and Other Microbial Communitiesmentioning
confidence: 84%
“…ABPs with different reactive electrophilic groups (e.g., fluorophosphonates [80], chloroisocoumarins [7] carbamates [81], β-lactams [82], β-lactones [82], triazole ureas [83][84][85], Michael acceptors [86], cyclophellitol epoxides and aziridine (see review [87]), disulfides and sulfonate esters [88]) have been developed to selectively study diverse enzyme families including serine hydrolases [7,74,80,89,90], cysteine proteases [91,92], kinases, metalloproteases [93], glutathione-S-transferases [94], cytochrome P450s [95], ATP-binding enzymes [96], or retaining glycosidases [87]. As discussed in more detail below, the most prominent ABP-targets in bacteria are penicillin-binding proteins [97,98], but the use of both broad-spectrum and target-selective ABPs for other bacterial enzymes in both imaging-related [12,84] and proteomic applications [90,99] is emerging.…”
Section: Activity-based Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we have recently identified a family of Fph hydrolases in S. aureus that function as lipid esterases and at least one of the family members has a role in host colonization 14 . We have performed screening studies using the triazole urea scaffold and found it difficult to identify highly selective inhibitors due to the highly conserved nature of this family 36 . Finally, there is currently no evidence that the DPP electrophile can function as a covalent inhibitor of lipid esterases, thus allowing us to assess the potential of the cyclic peptide to induce covalent bond formation for even sub-optimal electrophiles.…”
Section: Discussionmentioning
confidence: 99%